2013
DOI: 10.1107/s0907444913018714
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of gephyrin by AFM and SAXS reveals a mixture of compact and extended states

Abstract: Gephyrin is a trimeric protein involved in the final steps of molybdenum-cofactor (Moco) biosynthesis and in the clustering of inhibitory glycine and GABAA receptors at postsynaptic specializations. Each protomer consists of stably folded domains (referred to as the G and E domains) located at either terminus and connected by a proteolytically sensitive linker of ∼150 residues. Both terminal domains can oligomerize in their isolated forms; however, in the context of the full-length protein only the G-domain tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…S9), compared to the shallow minimum observed for GTF180-DN, may indicate that the full-length protein is slightly more flexible. Studies [22,23] have found a functional role for protein flexibility, although whether this also applies to glucansucrases such as GTF180 remains to be established. In this light, we considered performing SAXS measurements of GTF180 (or GTF180-DN) in the presence of its substrate sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…S9), compared to the shallow minimum observed for GTF180-DN, may indicate that the full-length protein is slightly more flexible. Studies [22,23] have found a functional role for protein flexibility, although whether this also applies to glucansucrases such as GTF180 remains to be established. In this light, we considered performing SAXS measurements of GTF180 (or GTF180-DN) in the presence of its substrate sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…The generated models may include folded regions or domains or even nucleic acids if needed; for oligomeric structures, asymmetric or symmetric multimers can be generated. The latter approach was employed in the study of a flexible protein gephyrin which consists of two folded domains (of which one forms a trimer) connected by a 150 amino acid residues linker [48]. The possibility of combining multiple independent pools further expands the range of applicability of EOM: in a recent study of a full-length mitochondrial glutaminase C [49], pools consisting of dimers, trimers and octamers were combined to explain how disordered regions influence enzymatic activity and the oligomeric state.…”
Section: Ensemble Approachmentioning
confidence: 99%
“…However, a recent structural analysis of gephyrin (expressed in E. coli) using atomic force microscopy and synchrotron X-ray scattering revealed that gephyrin forms trimers with multiple conformations, owing to partial flexibility of the C domain, and confirmed that the linker domain prevents E domain dimerization 174 , as was shown previously 164 . Visualization of gephyrin clusters in glycinergic synapses using super-resolution microscopy revealed a 1:1 stoichiometry with GlyRs 110 .…”
Section: Box 1: Gephyrin Structurementioning
confidence: 99%